Anode aluminum oxide PO protective film adhesive tape for battery and preparation method of anode aluminum oxide PO protective film adhesive tape

By developing a PO protective film tape in the field of anodized aluminum batteries, using acid-free acrylic polymer radical polymer polymerization technology and PO film substrates, the existing tape is difficult to meet the problems of oxidation prevention, acid-base solvent isolation and high-temperature performance at the same time, achieving efficient protection effects and meeting multiple performance requirements.

CN119529706APending Publication Date: 2025-02-28SUZHOU SHIHUA NEW MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411421031.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing protective film tape is difficult to meet the needs of anodized aluminum for oxidation prevention, acid-base solvent isolation and high-temperature performance during the processing of anodized aluminum in the battery field.

Method used

An anodized aluminum PO protective film tape for batteries is used, and the synthetic master glue includes mixed solvents, mixed monomers and initiators. Through acid-free acrylic polymer radical polymer polymer polymer radical polymer, tape with high cohesion strength and high temperature resistance is prepared, and PO film is used as the substrate to improve the weather resistance of the tape.

Benefits of technology

The tape has good cohesion properties, high temperature resistance, chemical resistance and other characteristics. It can maintain high viscoelasticity in the high temperature zone between 85 and 105°C, and exhibits excellent corrosion resistance in soaking in strong acids, strong alkalis and solvents, meeting multiple needs in battery processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529706A_ABST
    Figure CN119529706A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of pressure-sensitive adhesives, in particular to an anodic aluminum oxide PO protective film adhesive tape for a battery and a preparation method of the adhesive tape. The rubber comprises a synthetic rubber master batch and a curing agent, wherein the synthetic rubber master batch comprises a mixed solvent, a mixed monomer and a mixed initiator; the adhesive tape prepared by the invention has better cohesion performance, has the characteristics of high temperature resistance, chemical resistance and the like, and can meet various requirements of preventing a processing surface from being oxidized too fast, isolating strong acid, strong alkali and solvents and preventing the processing surface from being corroded by a solution in the preparation process of aluminum oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pressure-sensitive adhesives, in particular to an anodized aluminum PO protective film tape for batteries and a preparation method thereof. Background Art

[0002] Anodized aluminum is an aluminum surface treatment technology that uses an electrolytic oxidation process to significantly improve the wear resistance, corrosion resistance, and decorative properties of aluminum. It is widely used in many fields such as construction, aviation, and electronics. During the anodizing process, aluminum is placed in an electrolyte as an anode. After power is applied, a dense aluminum oxide film is formed on its surface. This film not only maintains the original lightness of aluminum, but also gives the material new functionality and aesthetics.

[0003] The application of anodized aluminum in the battery field, especially in lithium-ion batteries, is mainly concentrated in two aspects: one is as a coating layer for the positive electrode material of the battery, and the other is as a battery separator material. During the processing, grooves or planes will be milled on the surface of the anodized aluminum according to the different structural parts of the battery.

[0004] At the same time, during the processing of aluminum oxide, there are three stages: pretreatment, electrolytic oxidation, and sealing. Especially in the pretreatment stage of aluminum oxide, it needs to be cleaned with strong acid, strong alkali, and solvent. Therefore, it is necessary to stick a protective film tape on the milling groove or milling surface to prevent the process surface from being oxidized too quickly, and at the same time isolate strong acids, strong alkalis, and solvents to prevent the process surface from being corroded by the solution. The existing protective film tape is difficult to meet the various technical indicators of the aluminum oxide processing process at the same time.

[0005] In order to solve the above problems, the present invention provides an anodized aluminum PO protective film tape for a battery and a preparation method thereof. Summary of the invention

[0006] The object of the present invention is to provide an anodized aluminum PO protective film tape for batteries and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] Anodized aluminum PO protective film tape for batteries, comprising a synthetic masterbatch and a curing agent, wherein the synthetic masterbatch comprises, by weight:

[0009] 20 parts of mixed solvent

[0010] Mixed monomer 36.8 parts

[0011] Mixed initiator 0.21 parts;

[0012] The mixed solvent is a mixture of butyl acetate and ethyl acetate, and the mixing ratio of the two is 3:7;

[0013] The mass ratio of the curing agent is 0.2-2%.

[0014] More optimally, the mixed monomer is a mixture of glycidyl methacrylate, tert-butyl acrylate, cyclohexyl methacrylate, cyclohexyl acrylate, isobornyl acrylate, dicyclopentadienyl methacrylate, dicyclopentadienyl acrylate, isooctyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, glycidyl acrylate, cyclohexyl methacrylate, dicyclodecane methyl acrylate, octadecyl methacrylate, ethyl acetoacetate, and dimethylaminoethyl methacrylate.

[0015] More optimally, the initiator is a mixture of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide.

[0016] Preferably, the curing agent is isocyanate.

[0017] More optimally, the curing agent is a mixture of isocyanate and aluminum acetylacetonate.

[0018] More preferably, the substrate of the tape is PET, PI or PO.

[0019] The present invention also provides a method for preparing anodized aluminum PO protective film tape for batteries, comprising the following steps:

[0020] S1: 6 parts of butyl acetate and 14 parts of ethyl acetate are taken to form a mixed solvent, which is added into a four-necked reactor, and the temperature is adjusted to 40±5° C., and then the mixed monomers are added into the four-necked reactor and mixed to obtain a monomer mixed solution;

[0021] S2: Use a 1L four-necked flask, adjust the water bath temperature to 55-60°C, introduce nitrogen or other protective gas for 10 minutes, take 15 parts of the monomer mixed solution prepared in step S1 and add it to the four-necked flask, and add initiators 0.05 parts of azobisisobutyronitrile, 0.02 parts of azobisisoheptanenitrile and 0.1 parts of dibenzoyl peroxide, after the monomer mixed solution reacts with the initiator for 30 minutes, divide the remaining monomer mixed solution into two parts, continue to add the remaining monomer mixed solution twice, add half of the remaining mixed solution each time, and react for 30 minutes each time;

[0022] After the last monomer mixed solution is added, 0.01 parts of azobisisobutyronitrile, 0.01 parts of azobisisoheptanenitrile and 0.02 parts of dibenzoyl peroxide are added, the temperature is raised to 65-70°C, the drop rate is controlled at 5 parts / 1min, and the heating is stopped after keeping warm for 3 hours. During this process, protective gas is continuously introduced, and then refluxed and cooled to room temperature to obtain a synthetic masterbatch; at this time, the solid content is about 43%;

[0023] S3: Add a curing agent to the obtained synthetic masterbatch and apply it on the substrate to obtain a finished product of anodized aluminum PO protective film tape for batteries.

[0024] More optimally, the mixed monomer includes 5 parts of glycidyl methacrylate, 5 parts of tert-butyl acrylate, 2 parts of cyclohexyl methacrylate, 5 parts of cyclohexyl acrylate, 3.4 parts of isobornyl acrylate, 1.5 parts of dicyclopentadienyl methacrylate, 0.5 parts of dicyclopentadienyl acrylate, 3.3 parts of isooctyl acrylate, 1 part of hydroxyethyl acrylate, 2.7 parts of hydroxypropyl acrylate, 1.0 part of glycidyl acrylate, 0.7 part of cyclohexyl methacrylate, 2.4 parts of dicyclodecane methyl acrylate, 1.3 parts of octadecyl methacrylate, 1.5 parts of ethyl acetoacetate methacrylate, and 0.5 part of dimethylaminoethyl methacrylate.

[0025] More optimally, during coating, the adhesive layer thickness of the adhesive tape is 50 μm, and the substrate thickness is 150 μm.

[0026] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0027] (1) In the present invention, the acid-free acrylic polymer is polymerized by free radicals, and the monomer polymerization reaction is initiated by a thermal initiator, a photoinitiator, etc. Acid-free acrylic resin and functional monomers with high Tg, heat resistance and solvent resistance are selected, and the selected monomers have more unsaturated chemical bonds and free radicals. The copolymer is cross-linked by free radical polymerization, which improves the polymerization density of the copolymer, thereby improving the cohesive strength of the masterbatch; when the cohesive strength is better, the adhesive has higher creep resistance, reduces the slip amount of the adhesive, and improves the impact resistance of the adhesive. Therefore, the prepared masterbatch has better cohesive performance and has properties such as high temperature resistance and chemical resistance.

[0028] (2) In the present invention, the acid-free polymerization technology allows precise control of the molecular weight, molecular weight distribution and structure of the polymer, while the absence of an acid catalyst reduces environmental pollution and waste disposal problems.

[0029] (3) In the present invention, the prepared tape has good removability, and after removing the tape, there will be no residual adhesive on the bonding surface.

[0030] (4) In the present invention, a PO film (polyolefin film) with good heat resistance, weather resistance, solvent resistance and stretchability is selected as the tape substrate. The tape substrate can be recycled because the PO film (polyolefin film) has good solvent tolerance and the surface acrylic adhesive layer can be washed off in alkane or aromatic hydrocarbon solvents and recycled.

[0031] (5) In the present invention, the prepared adhesive tape has good high temperature range performance and can maintain high viscoelasticity at 85-105°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0033] Figure 1 The graphs are the temperature resistance performance of the masterbatches prepared in Example 3 and Example 6;

[0034] Figure 2 It is a line chart of the masterbatch rheological test data;

[0035] Figure 3 This is a schematic diagram of the tape fitting position when the tape is soaked;

[0036] Figure 4 It is a performance verification step diagram of Example 6 and Comparative Example;

[0037] Figure 5 This is a diagram of the immersion state of Example 6 and the comparative example in a silicon-free cleaning solution;

[0038] Figure 6 This is a diagram of the immersion state of Example 6 and the comparative example in a strong alkaline solution;

[0039] Figure 7 This is a diagram showing the immersion state of Example 6 and the comparative example in a degreasing cleaning agent;

[0040] Figure 8 It is a diagram of the immersion state of Example 6 and the comparative example in a strong acid solution. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The present invention provides an anodized aluminum PO protective film tape for a battery and a preparation method thereof, which mainly comprises the following steps:

[0043] Step 1:

[0044] A mixed solvent (6 parts of butyl acetate, 14 parts of ethyl acetate) was added into a four-necked reactor, and the temperature was adjusted to 40±5°C. A mixed monomer was formed by adding 5 parts of glycidyl methacrylate, 5 parts of tert-butyl acrylate, 2 parts of cyclohexyl methacrylate, 5 parts of cyclohexyl acrylate, 3.4 parts of isobornyl acrylate, 1.5 parts of dicyclopentadienyl methacrylate, 0.5 parts of dicyclopentadienyl acrylate, 3.3 parts of isooctyl acrylate, 1 part of hydroxyethyl acrylate, 2.7 parts of hydroxypropyl acrylate, 1.0 part of glycidyl acrylate, 0.7 part of cyclohexyl methacrylate, 2.4 parts of dicyclodecane methyl acrylate, 1.3 parts of octadecyl methacrylate, 1.5 parts of ethyl acetoacetate methacrylate, and 0.5 parts of dimethylaminoethyl methacrylate, and the mixture was added into the mixed solvent and mixed evenly.

[0045] Step 2:

[0046] Preparation of acrylic acid copolymer

[0047] A 1L four-necked flask was used, the water bath temperature was adjusted to 55-60°C, and a protective gas such as nitrogen was introduced for 10 minutes. 15 parts of the monomer mixed solution after mixing in step 1 were taken out, 0.05 parts of azobisisobutyronitrile, 0.02 parts of azobisisoheptanenitrile, and 0.1 parts of dibenzoyl peroxide were added, and the reaction lasted for 30 minutes. The remaining monomer mixed solution was divided into two parts, and half of the monomer mixed solution was added each time. Each reaction lasted for 30 minutes. After the last half of the monomer mixed solution was added, 0.01 parts of azobisisobutyronitrile, 0.01 parts of azobisisoheptanenitrile, and 0.02 parts of dibenzoyl peroxide were added. The temperature was raised to 65-70°C, and the dropping speed was controlled at 5 parts / 1min. After keeping warm for 3 hours, the heating was stopped. During this process, the protective gas was continuously introduced, and then the mixture was refluxed and cooled to room temperature to obtain an acrylic copolymer with a solid content of about 43%.

[0048] Finally, a curing agent is added to the acrylic copolymer and coated on the substrate to obtain a finished tape.

[0049] In order to verify the performance and effect of the adhesive tape prepared by the present invention, the present invention provides several embodiments and comparative examples for testing and comparison. The basic technical indicators to be achieved are: peel strength for aluminum plate>2000gf / in, for aluminum plate at high temperature>1000gf / in; acid immersion, alkali immersion, solvent residual adhesive rate<1%; the adhesive tape does not deform or wrinkle at high temperature or after cleaning.

[0050] The materials and sources used in the examples and comparative examples are shown in Table 1.

[0051] Table 1 Materials and sources

[0052]

[0053]

[0054]

[0055] In each embodiment of the present invention, the contents of the mixed solvent, the mixed monomer and the mixed initiator are the same, that is, the prepared synthetic masterbatch is the same, and the thickness of the glue layer is 50 μm. The difference is that:

[0056] Example 1: Add 0.2% by mass of isocyanate into the synthetic masterbatch.

[0057] Example 2: Add 0.5% by mass of isocyanate into the synthetic masterbatch.

[0058] Example 3: Add 2% by mass of isocyanate into the synthetic masterbatch.

[0059] Example 4: Add 0.5% epoxy resin and 0.5% isocyanate in a mass ratio to the synthetic masterbatch.

[0060] Example 5: Add 1% epoxy resin and 0.5% isocyanate in a mass ratio to the synthetic masterbatch.

[0061] Example 6: Add 1% epoxy resin and 1% isocyanate in a mass ratio to the synthetic masterbatch.

[0062] The peel strength and residual adhesive rate of the adhesive layers prepared in several embodiments were tested, and the results are shown in Table 2.

[0063] Specific test method

[0064] Peel force test method: GB / T 2792-2014 "180° peel strength test for pressure-sensitive adhesive tapes"

[0065] Residual glue rate test method:

[0066] 1. Apply a 50μm adhesive layer on a 50m PET substrate, with a total thickness of 100m. (The adhesive layer thickness is consistent with the adhesive layer thickness of the tape)

[0067] 2. Take a clean steel plate or aluminum plate with a size of 50mm*50mm*1mm, and then weigh it and record it as m1;

[0068] 3. Stick the adhesive surface on a clean steel plate or aluminum plate with a bonding area of ​​25mm*25mm. Leave a 10mm lead on the tape for easy peeling. Then weigh and record it as m2. After sticking, leave it at room temperature for 24 hours. Then place it at 90℃ / 90%RH for 24 hours;

[0069] 4. Take out the sample and place it at room temperature for 2 hours, then peel it off quickly. The weight after peeling is recorded as m3;

[0070] 5. Residual glue rate n = (m3-m1) / (m2-m1)*100%.

[0071] Table 2 Peel strength and residual adhesive rate of adhesive layer obtained in each embodiment

[0072] project Peel strength to SUS Peel strength to AL Ratio of residual adhesive to SUS Ratio of residual adhesive to AL Example 1 4450 3541 21% 15% Example 2 3489 2945 8.7% 4.4% Example 3 2712 2204 0.5% 0 Example 4 3654 3214 11% 2.7% Example 5 3312 2854 1.2% 0.2% Example 6 2766 2513 0.2% 0

[0073] As can be seen from Table 2, the effects of Example 3 and Example 6 are better, among which Example 6 has the best effect and the lowest residual glue rate. Based on Example 3 and Example 6, the present invention verifies the heat resistance of the masterbatch prepared, and the results are as follows: Figure 1 As shown, it can be seen that the temperature resistance of Example 6 on SUS and AL is stronger than that of Example 3.

[0074] Therefore, the present invention is based on Example 6 and designs adhesive tapes based on different types of substrates, and the thickness of the substrates is 150 μm.

[0075] Prior to this, the present invention conducted rheological data testing on the prepared masterbatch, and the test results were as follows: Figure 2 As shown. Figure 2 It can be seen that the masterbatch has a higher storage modulus at room temperature. At the same time, in the high temperature range of 85-150℃, the storage modulus curve basically maintains a balance, and has good high temperature resistance.

[0076] Example 6: Using PO (polyolefin) substrate.

[0077] Comparative Example 1: PET (polyethylene terephthalate) substrate was used.

[0078] Comparative Example 2: Using PI (polyimide) substrate.

[0079] The tapes prepared in Example 6, Comparative Examples 1 and 2 were attached to the target metal, and then immersed in a silicon-free cleaning agent for 5 minutes, in a strong alkaline solution (NaOH) for 1 hour, in a degreasing cleaning agent for 1 hour, and in a 95°C strong acid solution (oxalic acid) for 1 hour, and then the surface conditions were observed. The specific attachment method of the tape during immersion was as follows: Figure 3 The test results are shown in Table 4, and the immersion process is shown in Figures 4 to 8 shown.

[0080] In addition, the present invention also tests the mechanical properties of the three substrates after high temperature and high humidity treatment, and the results are shown in Table 3.

[0081] Table 3 Performance test results of each substrate after immersion

[0082]

[0083] From the results in Table 3, it can be seen that after being treated with high temperature and high humidity, PET and PI films have obvious problems of becoming brittle and having reduced toughness, while PO film still has good toughness after being treated with high temperature and high humidity. Therefore, the tape using PO film has no obvious wrinkles and liquid seepage problems after being soaked in chemical reagents.

[0084] Table 4 Surface conditions after immersion of Example 6 and Comparative Examples

[0085]

[0086] From Table 4, Figures 2 to 6 It can be seen from the results that, under the same conditions, the tape made of PO substrate has the best performance, good cohesive performance, high temperature resistance, chemical resistance and other properties. It can meet the needs of preventing the process surface from oxidizing too quickly during the preparation of alumina, and at the same time isolate strong acids, strong alkalis and solvents to prevent the process surface from being corroded by the solution.

[0087] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0088] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An anodized aluminum PO protective film tape for batteries, characterized in that: The method comprises a synthetic masterbatch and a curing agent, wherein the synthetic masterbatch comprises, by weight: 20 parts of mixed solvent Mixed monomer 36.8 parts Mixed initiator 0.21 parts; Wherein, the mixed solvent is a mixture of butyl acetate and ethyl acetate, and the mixing ratio of the two is 3:7; The mass ratio of the curing agent is 0.2-2%.

2. The anodic aluminum oxide PO protective film tape for batteries according to claim 1, characterized in that: The mixed monomer is a mixture of glycidyl methacrylate, tert-butyl acrylate, cyclohexyl methacrylate, cyclohexyl acrylate, isobornyl acrylate, dicyclopentadienyl methacrylate, dicyclopentadienyl acrylate, isooctyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, glycidyl acrylate, cyclohexyl methacrylate, dicyclodecane methyl acrylate, octadecyl methacrylate, ethyl acetoacetate, and dimethylaminoethyl methacrylate.

3. The PO protective film tape for anodized aluminum for batteries according to claim 1, characterized in that: The initiator is a mixture of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide.

4. The anodic aluminum oxide PO protective film tape for batteries according to claim 1, characterized in that: The curing agent is isocyanate.

5. The anodic aluminum oxide PO protective film tape for batteries according to claim 1, characterized in that: The curing agent is a mixture of isocyanate and aluminum acetylacetonate.

6. The anodized aluminum PO protective film tape for batteries according to claim 1, characterized in that: The substrate of the adhesive tape is a polyolefin substrate.

7. A method for preparing anodized aluminum PO protective film tape for batteries, characterized in that: The steps include: S1: 6 parts of butyl acetate and 14 parts of ethyl acetate are taken to form a mixed solvent, which is added into a four-necked reactor, and the temperature is adjusted to 40±5° C., and then the mixed monomers are added into the four-necked reactor and mixed to obtain a monomer mixed solution; S2: Use a 1L four-necked flask, adjust the water bath temperature to 55-60°C, introduce nitrogen protective gas for 10 minutes, take 15 parts of the monomer mixed solution prepared in step S1 and add it to the four-necked flask, and add initiators 0.05 parts of azobisisobutyronitrile, 0.02 parts of azobisisoheptanenitrile and 0.1 parts of dibenzoyl peroxide. After the monomer mixed solution reacts with the initiator for 30 minutes, the remaining monomer mixed solution is divided into two parts, and the remaining monomer mixed solution is added twice, half of the remaining mixed solution is added each time, and each reaction is 30 minutes; After the last monomer mixed solution is added, 0.01 parts of azobisisobutyronitrile, 0.01 parts of azobisisoheptanenitrile and 0.02 parts of dibenzoyl peroxide are added, the temperature is raised to 65-70°C, the drop rate is controlled at 5 parts / 1min, and the heating is stopped after keeping warm for 3 hours. During this process, protective gas is continuously introduced, and then refluxed and cooled to room temperature to obtain a synthetic masterbatch; at this time, the solid content is 43%; S3: Add a curing agent to the obtained synthetic masterbatch and apply it on the substrate to obtain a finished product of anodized aluminum PO protective film tape for batteries.

8. The anodic aluminum oxide PO protective film tape for batteries according to claim 7, characterized in that: The mixed monomer includes 5 parts of glycidyl methacrylate, 5 parts of tert-butyl acrylate, 2 parts of cyclohexyl methacrylate, 5 parts of cyclohexyl acrylate, 3.4 parts of isobornyl acrylate, 1.5 parts of dicyclopentadienyl methacrylate, 0.5 parts of dicyclopentadienyl acrylate, 3.3 parts of isooctyl acrylate, 1 part of hydroxyethyl acrylate, 2.7 parts of hydroxypropyl acrylate, 1.0 part of glycidyl acrylate, 0.7 part of cyclohexyl methacrylate, 2.4 parts of dicyclodecane methyl acrylate, 1.3 parts of octadecyl methacrylate, 1.5 parts of ethyl acetoacetate methacrylate, and 0.5 part of dimethylaminoethyl methacrylate.

9. The PO protective film tape for anodized aluminum for batteries according to claim 7, characterized in that: During coating, the adhesive layer thickness of the adhesive tape is 50 μm, and the substrate thickness is 150 μm.